Volunteering and the Sustainable Development Goals: an opportunity to move beyond boundaries. (1st July 2020) - Ellis Paine, Angela; Allum, Cliff; Beswick, Danielle; Lough, Benjamin J.
Abstract : There is growing recognition of the role that volunteering can play in the implementation of the Sustainable Development Goals (SDGs). Evidence of its contribution, however, remains relatively weak, including for countries in the Global North such as the UK. This is compounded by limited collaboration between those concerned with volunteering and those concerned with development. The SDGs provide an opportunity to bring together research, policy and practice on volunteering and development, and on international and 'domestic' volunteering, enabling valuable interdisciplinary learning.